Cartographic strategies: subjective world views - Asselberghs, Herman; Devleminck, Steven (Leuven Acco, 2008)
Cartographic Strategies. Subjective Worldviews is part of An Anthropology of World Mapping, a three-year, interdisciplinary research project (2004-2007). Located at the intersection between art and science, between fact and fantasy, between print and the digital, this project pushes towards a fluid cartography for the new millennium.